Developing habit-based health behaviour change interventions: twenty-one questions to guide future research. Issue 4 (3rd April 2023) - Gardner, Benjamin; Arden, Madelynne A.; Brown, Daniel; Eves, Frank F.; Green, James; Hamilton, Kyra; Hankonen, Nelli; Inauen, Jennifer; Keller, Jan; Kwasnicka, Dominika; Labudek, Sarah; Marien, Hans; et al.
Abstract: Objective: Habitual behaviours are triggered automatically, with little conscious forethought. Theory suggests that making healthy behaviours habitual, and breaking the habits that underpin many ingrained unhealthy behaviours, promotes long-term behaviour change. This has prompted interest in incorporating habit formation and disruption strategies into behaviour change interventions. Yet, notable research gaps limit understanding of how to harness habit to change real-world behaviours. Methods: Discussions among health psychology researchers and practitioners, at the 2019 European Health Psychology Society 'Synergy Expert Meeting', generated pertinent questions to guide further research into habit and health behaviour. Results: In line with the four topics discussed at the meeting, 21 questions were identified, concerning: how habit manifests in health behaviour (3 questions); how to form healthy habits (5 questions); how to break unhealthy habits (4 questions); and how to develop and evaluate habit-based behaviour change interventions (9 questions). Conclusions: While our questions transcend research contexts, accumulating knowledge across studies of specific health behaviours, settings, and populations will build a broader understanding of habit change principles and how they may be embedded into interventions. We encourage researchers and practitioners to prioritise these questions, to further theory and evidence around how to create long-lasting health behaviour change.